Thermal and mechanical characterization of high performance polymer fabrics for applications in wearable devices - Aaditya A. Candadai (Nature Portfolio, 2021)
Abstract With advances in flexible and wearable device technology, thermal regulation will become increasingly important. Fabrics and substrates used for such applications will be required to effectively spread any heat generated in the devices to ensure user comfort and safety, while also preventing overheating of the electronic components. Commercial fabrics consisting of ultra-high molecular weight polyethylene (UHMW-PE) fibers are currently used in personal body armor and sports gear owing to their high strength, durability, and abrasion resistance. In addition to superior mechanical properties, UHMW-PE fibers exhibit very high axial thermal conductivity due to a high degree of polymer chain orientation. However, these materials have not been widely explored for thermal management applications in flexible and wearable devices. Assessment of their suitability for such applications requires characterization of the thermal and mechanical properties of UHMW-PE in the fabric form that will ultimately be used to construct heat spreading materials. Here, we use advanced techniques to characterize the thermal and mechanical properties of UHMW-PE fabrics, as well as other conventional flexible materials and fabrics. An infrared microscopy-based approach measures the effective in-plane thermal conductivity, while an ASTM-based bend testing method quantifies the bending stiffness. We also characterize the effective thermal behavior of fabrics when subjected to creasing and thermal annealing to assess their reliability for relevant practical engineering applications. Fabrics consisting of UHMW-PE fibers have significantly higher thermal conductivities than the benchmark conventional materials while possessing good mechanical flexibility, thereby showcasing great potential as substrates for flexible and wearable heat spreading application.